Determinant Analysis of Secondhand Clothing Traders’ Income at Pasar Senggol Batubulan, Gianyar Regency - I Putu Agung Arma Wisswabawa; Made Heny Urmila Dewi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The trade of secondhand clothing at Pasar Senggol Batubulan, Gianyar Regency, has become a rapidly growing economic activity and an alternative source of income, particularly amidst limited formal employment opportunities. However, the income of secondhand clothing traders tends to fluctuate and is influenced by several internal business factors. This study aims to analyze the influence of price, business capital, working hours, and product quality on the income of secondhand clothing traders. An associative quantitative approach was used, involving 61 traders selected through a saturated sampling technique. The data analysis method applied is multiple linear regression. The findings reveal that price, capital, working hours, and product quality simultaneously have a significant effect on traders’ income. Partially, all four variables also show a significant influence. Product quality is the most dominant factor affecting income, followed by capital, working hours, and price. Adequate capital enables traders to increase stock and improve product quality. Longer working hours provide greater opportunities to serve consumers, while competitive pricing boosts sales capacity. These findings underscore the importance of managing internal business factors to enhance income and contribute to the economic empowerment of communities in the informal sector.